La literatura catalana i el cinema - Pérez, F. Xavier (Caplletra. Revista Internacional de Filologia, 2002)
This article offers a historical summary of the relationship between the Catalan narrative and dramatic literature, and their film versions from the beginnings of the cinema in Catalonia, going through the Franco period, the proposals of the poetic avant-garde and the cultural recovery of the 1980s, to the current narrative and non-narrative genres, in which the trend is to trascend the audiovisual “version” with an autonomous film conception.